Footwear alterations after first metatarsophalangeal joint arthrodesis - May, Hasan; Ünal, Melih; Katı, Yusuf Alper; Gümüşsuyu, Gürkan; Köse, Özkan (The European Research Journal, 2022)
Objectives: This study aimed to examine the footwear alterations following first metatarsophalangeal (MTP1) joint arthrodesis. Methods: A retrospective review was performed on 37 (42 feet) patients who underwent MTP1 joint arthrodesis between January 2014 and January 2019 in our institution. Functional outcomes were assessed with the American Orthopedic Foot and Ankle Society Hallux metatarsophalangeal–interphalangeal (AOFAS-MTP-IP) scale, and the pain was assessed using the visual analog scale (VAS). Besides, time to return regular footwear, shoe preferences, the cosmetic appearance of the feet were evaluated and compared with preoperative status. Results: The mean follow-up time was 12.0 ± 16.5 months. The preoperative AOFAS-MTP-IP scale improved from 46.6 ± 7.0 points to 86.2 ± 7.2 points (p =0.001), and VAS decreased from 6.3 ± 1.8 points to 1.4 ± 0.5 points (p =0.001). There was non-union in three (7.1%) feet, and the mean union time for the rest of the feet was 8.2 ± 1.1 weeks. No other complications were seen. The mean time for resuming regular footwear was 11.8 ± 2.6 weeks. Patients’ perception of the appearance of their feet improved from 3.9 ± 2.8 to 9.0 ± 0.7 points (p =0.001). Twenty-nine (78.6%) patients (33 feet) reported that there was no restriction in footwear compared to the past, but 8 (21.4%) patients had to choose specific types and models. None of the patients had to use modified or custom-made shoes. There was significant change in the heel height preferences after the surgery (p =0.004). 18 (52.4%) patients had to choose shorter heel height than preoperative preferences, whereas 19 (47.6%) patients’ preference did not change. Almost all patients, 36 (97.6%) were using athletic shoes in their routine daily life. Conclusions: MTP1 joint arthrodesis is a reliable method that controls pain and increases function with a low rate of complications. However, significant alterations in footwear preferences may occur. Patients should be informed adequately about these outcomes to modify patient expectations.